(untitled) (Docentes 2.0 Journal, 2020)
This article is based on the influence of Information and Communication Technology to strengthen the Teaching and Learning Process in students that have visual impairment. The research is based on the bases of Downes and Siemens’ connectivism allowing to articulate new forms of knowledge; blind people confront many challenges day by day to get by on their own, from the inadequate physical space for their transport, as well as in the development of activities in education, that is why we try to describe the contributions that the new technologies that exist in the environment provide and the benefits that they generate in the teaching and learning process of people with this type of disability. The methodology that was used corresponded to a qualitative approach of documentary focus, as well as the application of an interview for the process of data collection. The results obtained showed that the existence of a variety of computer resources, such as Talkback, Nvda, Vocalizer, Jaws, would allow the student’s independence in the learning process, generating a level of autonomy to enhance their cognitive development. Finally, it can be stated that the insertion of ICT in the processes of educational inclusion allows to reduce the barriers that are presented in the development of the formation of the teachers, managing to apply inclusive activities with the use of technology in the development of the class, understanding that there is a diverse society with different ways of thinking, learning and acting.